Pengaruh Perputaran Modal Kerja, Pertumbuhan Penjualan dan Ukuran Perusahaan Terhadap Kebijakan Dividen Pada Perusahaan Sektor Pertanian Yang Terdaftar di Bursa Efek Indonesia Periode 2017-2021 - Sijabat, Pinta Juliani; Hidayat, Ferry (Expensive: Jurnal Akuntansi dan Keuangan, 2023)
This study aims to determine and also analyze the Effect of Working Capital Turnover, Sales Growth and Company Size on Dividend Policy in Agricultural Sector Companies Listed on the Indonesia Stock Exchange for the 2017-2021 Period. The research approach used is a quantitative approach. The type of research used is descriptive quantitative research and the nature of this research is explanatory research. The analysis used in this study is multiple linear regression analysis, in which sales growth and company size have an effect on dividend policy, while the rest of working capital turnover has no effect on dividend policy. Simultaneously shows the results that working capital turnover, sales growth and company size have a significant effect on dividend policy